MoS2: a two-dimensional hole-transporting material for high-efficiency, low-cost perovskite solar cells. (20th March 2018) - Kohnehpoushi, Saman; Nazari, Pariya; Nejand, Bahram Abdollahi; Eskandari, Mehdi
Abstract: In this work MoS2 thin film was studied as a potential two-dimensional (2D) hole-transporting material for fabrication of low-cost, durable and efficient perovskite solar cells. The thickness of MoS2 was studied as a potential factor in reaching high power conversion efficiency in perovskite solar cells. The thickness of the perovskite layer and the different metal back contacts gave distinct photovoltaic properties to the designed cells. The results show that a single sheet of MoS2 could considerably improve the power conversion efficacy of the device from 10.41% for a hole transport material (HTM)-free device to 20.43% for a device prepared with a 0.67 nm thick MoS2 layer as a HTM. On the back, Ag and Al collected the carriers more efficiently than Au due to the value of their metal contact work function with the TiO2 conduction band. The present work proposes a new architecture for the fabrication of low-cost, durable and efficient perovskite solar cells made from a low-cost and robust inorganic HTM and electron transport material.